Sosialisasi Pemanfaatan Limbah Plastik Sebagai Wadah Tanam Sayur Di SDN Sebani - Wahyudi Wahyudi; Rif’an Hariri; Khoirun Nisa'; Chusnul Chotima; khusnul Khotimah; Revin Fajariyatul Chuzairoh; Helmawan Nugroho; Wahyu Azalea Az'zahra (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2026)
Sebani Village, which is located in Sumobito District, Jombang Regency, East Java, has an area of about 6.45 km² with a population of around 4,650 people. Most people depend on the agricultural sector for their livelihood, with the main commodities being rice, corn, and horticultural vegetables such as chili, tomatoes, and kale. However, the problem here is regeneration in preparing prospective farmers in the coming masses, besides other problems faced in the village such as environmental problems in the form of the accumulation of household plastic waste. Single-use plastics, such as mineral water bottles, plastic cups, and detergent packaging, are widely found and are often simply thrown away without further processing. Therefore, to solve the problems that exist in Sebani village in the regeneration of farmers and plastic waste which only becomes waste without further processing so that it becomes more useful, a socialization program for planting vegetables with the use of plastic waste at SDN Sebani and MI Bustanul Ulum Sebani is very strategic. The qualitative research method used in this case combines interactive lectures, demonstrations, and hands-on practice, the results of the study show that the students' understanding of the benefits of growing vegetables using plastic waste media Students show a sense of pride and joy because they have successfully grown vegetables for the first time. Some students also expressed their desire to take care of the plant so that it can grow until harvest.